Adipose tissue stromal vascular fraction and adipose tissue stromal vascular fraction plus platelet‐rich plasma grafting: New regenerative perspectives in genital lichen sclerosus. Issue 6 (22nd September 2020) - Tedesco, Marinella; Bellei, Barbara; Garelli, Valentina; Caputo, Silvia; Latini, Alessandra; Giuliani, Massimo; Cota, Carlo; Chichierchia, Giuseppina; Romani, Claudia; Foddai, Maria Laura; Cristaudo, Antonio; Morrone, Aldo; et al.
Abstract: Lichen sclerosus (LS) is a chronic relapsing, inflammatory skin disorder usually involving the anogenital region of both sexes lacking a resolutive therapy. This study compared adipose tissue derived‐stromal vascular fraction (AD‐SVF) and AD‐SVF‐enriched platelet‐rich plasma (PRP) therapy in the management of genital LS patients. Additionally, in vitro evaluation of cells and growth factors contained in the injected SVF has been evaluated as possible predictive factors for treatment outcome. The study population was 40 patients diagnosed with LS who were symptomatic despite medical treatment. Patients (age 43‐78 years) randomized into two groups using a 1:1 allocation ratio, were evaluated clinically and assessing dermatology life quality index (DLQI) before and 6 months after treatment. Both procedures demonstrated a strong safety profile with no complications linked to the therapy. After 6 months, both treatments allowed for a significant improvement respect to baseline. Combinatory therapy demonstrated decreased efficacy in late stage patients. No correlations have been found between clinical and biological findings. AD‐SVF and AD‐SVF plus PRP are safe and effective regenerative approaches for genital LS patients. Clinical results support the preferential use of combinatory therapy for early stage patients confirming a synergic effect of AD‐SVF and PRP. In contrast, AD‐SVF plus PRP is discouraged for late stage patients.